Simvastatin Modulates Interaction Between Vascular Smooth Muscle Cell/Macrophage and TNF-α–Activated Endothelial Cell. Issue 5 (May 2018) - Chu, Fujiang; Wang, Min; Ma, Hongyan; Zhu, Jiayong
Abstract : Abstract: Cellular interactions between endothelial cell (EC) and vascular smooth muscle cell (VSMC)/macrophages seem to be greatly changed under inflammatory conditions. Although simvastatin could regulate inflammatory transcription factors in EC and VSMC and also could inhibit leukocyte–endothelium interaction, whether it could modulate VSMC/macrophage functions that are induced by tumor necrosis factor-α (TNF-α)–activated EC remained unclear. The purpose of this study was to investigate the effects of simvastatin on VSMC/macrophage functions, which are induced by TNF-α–activated EC in coculture system in vitro. The results showed that under noncontacting conditions, simvastatin could reduce the proliferation, apoptosis, and TNF-α, IL-6, and vascular endothelial growth factor secretion both in VSMC and macrophage, which is induced by TNF-α–activated EC. And a hypothesis that simvastatin regulates the interactions and the soluble factors between EC and VSMC/macrophages could be drawn. And that might be a potential anti-atherosclerosis mechanism of simvastatin.